Total RNA content in buffalo oocytes and different stages of preimplantation embryos produced in vitro - RAJHANS, RAJIB; KUMAR, G SAI; CHANDRA, VIKASH; MISHRA, ASHISH; SHARMA, G TARU (The Indian Journal of Animal Sciences, 2011)
Total RNA content can be used as a preliminary indicator of intrinsic quality of in vitro matured (IVM) oocytes and preimplantation stage embryos. The present study was conducted to assess the total RNA content of different preimplantation stage buffalo (Bubalus bubalis) embryos and to study the effect of vitrification on the total RNA content of in vitro matured buffalo oocytes. The amount of total RNA in the pools of immature oocytes (IM, 120), in vitro matured oocytes (MO, 120), preimplantation stage embryos 8–16 cell (8–16,47), morula (M, 13), blastocyst (B,7) as well as in the in vitro matured and vitrified oocytes (MV, 120) was quantified spectrophotometrically. Total RNA content (ng/oocyte or embryo) was reduced slightly from immature (2.24±0.40) to matured oocyte (1.66±0.53) followed by a significant (P